2003
DOI: 10.1097/00008483-200303000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Heart Rate Recovery After Cardiac Rehabilitation

Abstract: Exercise training in a cardiac rehabilitation program results in HRR improvement. As a simple parameter for assessing autonomic tone, HRR may be used in a cardiac rehabilitation facility to identify patients with higher risk profiles, and can be useful for evaluating patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 12 publications
2
36
1
2
Order By: Relevance
“…This has important clinical applications because the speed of HRR is a clinical variable that may be useful for population screening. Although HRR is modifiable by, for example, physical activity interventions, [33][34][35][36] whether modifying HRR directly reduces mortality requires further study. Future intervention studies should be designed to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…This has important clinical applications because the speed of HRR is a clinical variable that may be useful for population screening. Although HRR is modifiable by, for example, physical activity interventions, [33][34][35][36] whether modifying HRR directly reduces mortality requires further study. Future intervention studies should be designed to explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on exercise training provide supportive evidence that heart rate recovery can be improved 20,21 ; however, neither study was large enough to assess for effects on mortality. Likewise, neither study focused on patients with a distinctly abnormal heart rate recovery.…”
Section: Centers Other Than the Cleveland Clinic Have Submittedmentioning
confidence: 99%
“…Studies showed that HRR improves with weight loss, exercise training, and cardiac rehabilitation [18,21,31,32]. Burger, et al [33] and the Diabetes Control and Complications (DCC) trial [34] found that stringent glycemic control may improve autonomic dysfunction and even a modest reduction in the mean HbA1c produced favorable effects on Cardiac Autonomic Neuropathy (CAN).…”
Section: Conflict Of Interestmentioning
confidence: 99%